Criminal Law Reform and the Quest for Justice and Legal Certainty: A Normative Analysis in the Indonesian Context - Jamaluddin (www.amertainstitute.com, 2026)
Criminal law reform represents a strategic effort to modernize the legal system in response to evolving societal dynamics, particularly in achieving a balance between justice and legal certainty. In Indonesia, the existing criminal law framework, largely influenced by colonial legacies, is often considered inadequate in addressing contemporary legal challenges, including the rise of complex and transnational crimes. This study aims to examine the urgency of criminal law reform from the perspectives of justice and legal certainty and to identify the ideal direction for such reform. The research employs a normative juridical method, utilizing statutory and conceptual approaches through an extensive review of legal doctrines, regulations, and scholarly literature. The findings reveal that criminal law reform is essential to reconcile the tension between substantive justice and formal legal certainty, which often coexist in imbalance within legal practice. The study highlights the importance of integrating restorative justice principles, enhancing the clarity and consistency of legal norms, and strengthening law enforcement institutions to ensure fair and predictable legal outcomes. Furthermore, legal reform must encompass not only regulatory changes but also institutional improvement and the development of legal culture within society. In conclusion, a comprehensive and adaptive approach to criminal law reform is necessary to establish a legal system that is responsive, equitable, and capable of addressing modern societal needs while maintaining legal certainty